Gingival crevicular fluid protein content and alkaline phosphatase activity in relation to pubertal growth phase - Perinetti, Giuseppe; Franchi, Lorenzo; Castaldo, Attilio; Contardo, Luca (The Angle orthodontist, 2012)
To evaluate gingival crevicular fluid (GCF) protein content and alkaline phosphatase (ALP) activity in growing subjects in relation to stages of skeletal maturation, ie, the growth phase, as prepubertal, pubertal, and postpubertal. Fifty healthy growing subjects (31 girls and 19 boys; age range, 7.8-17.7 years) were enrolled in this study that followed a double-blind, prospective, cross-sectional design. Collection of GCF was performed at the mesial and distal sites of both central incisors, for the maxilla and mandible. Growth phase was assessed through the cervical vertebral maturation method. GCF parameters were expressed as total protein content, total ALP activity, and normalized ALP activity. The total GCF protein content was similar between the different growth phases. On the contrary, the total ALP activity showed a peak for the pubertal growth phase. The normalized GCF ALP activity was only poorly associated with growth phase. No differences were seen between the maxillary and mandibular sites, or between the sexes, for any GCF parameter. The total GCF protein content is not sensitive to the growth phase. However, GCF ALP activity has potential as a diagnostic aid for identification of the pubertal growth phase in individual subjects when expressed as total, but not normalized, values.